ENVIRONMENTAL MANAGEMENT ACCOUNTING (EMA) IN DISCLOSING ENVIRONMENTAL RISKS UNDER THE METRICS AND TARGETS PILLAR OF THE TASK FORCE ON CLIMATE-RELATED FINANCIAL DISCLOSURES (TCFD): ANALYSIS OF CONTRIBUTION TO SDG 13 (CLIMATE ACTION) IN COAL COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2022–2024 - Radia, Siti; Amaliah, Tri Handayani; Mahdalena, Mahdalena (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the role of Environmental Management Accounting (EMA) in disclosing environmental risks under the metrics and targets pillar of the Task Force on Climate-related Financial Disclosures (TCFD), as well as its contribution to the achievement of SDG 13 (Climate Action) in coal companies listed on the Indonesia Stock Exchange during 2022–2024. This research employs a descriptive quantitative approach using secondary data obtained from sustainability reports. The sample consists of 17 coal companies selected through purposive sampling, resulting in 51 observations. Data analysis is conducted using content analysis with a dummy scoring method based on 17 indicators of the TCFD metrics and targets pillar. The results indicate that the level of environmental risk disclosure shows an increasing trend, from 37.71% in 2022 to 48.44% in 2024. However, the overall level remains moderate, indicating that companies are still in a transition phase toward more mature climate reporting practices. Basic indicators such as total emissions and Scope 1 and Scope 2 emissions are widely disclosed, while advanced indicators such as Scope 3 emissions and emission reduction targets remain limited. The findings also reveal that the contribution to SDG 13 is uneven: strong in providing baseline emission data, moderate in emission intensity efficiency, and weak in comprehensive inventory and long-term mitigation strategies. Furthermore, companies are categorized into three groups—best practice, intermediate, and resistant—based on their level of disclosure and EMA readiness. Companies with more developed EMA systems demonstrate stronger contributions to climate action. Overall, the study concludes that the coal sector shows positive but not yet optimal alignment with SDG 13, requiring improvements in methodological transparency, Scope 3 measurement, and science-based emission targets.